Krisis Kasih dalam Gereja sebagai Refleksi Bagi Kehidupan Orang Percaya Masa Kini - Djone georges nicolas; Soneta Sang Surya Siahaan; Timothy Amien (CV. Syntax Corporation Indonesia, 2022)
God's Word clearly and straightforwardly states that people who have believed in Christ, in other words who have come out of darkness or death, and entered into light or life have an awareness of the obligation to show love through sacrifice for others as a representation of Christ's love. real and perfect (John 3:14-16 (NKJV). This has been proven by the early church, Christ's faithful disciples in serving one another without regard to their own egos, but on the contrary were willing to sacrifice personal property for the sake of meeting the needs of others, so that harmony and unity in brotherly love are created for the glory of the Kingdom of God Acts 2:42-47 (NIV). The purpose of this study is to analyze the causes of the crisis of love in the lives of believers today. Christianity is not can be separated from the person of Christ where He is the central figure Research approach method The method used is descriptive qualitative with data collection through various sources such as the Bible, books, journals, interviews, and other sources that are related to the topic of study. As a result, firstly, the purpose of some believers' lives is not to glorify Christ, but rather for their own interests so that they become a stumbling block. Second, the value of the life lived by Christians is no different from the value of the life of the world (outside of Christianity). it can be concluded that there are two causes of the crisis of love in the lives of believers today, namely: First, the purpose of the life that some believers live is not to glorify Christ, but rather for their own interests so that they become a stumbling block and shift from God's mission.